Effect of addition of whey protein isolate on spray-drying behavior of honey with maltodextrin as a carrier material - Shi, Q.; Fang, Zhongxiang; Bhandari, B. (Taylor & Francis, 2013)
The efficiency of two drying carriers, namely whey protein isolate (WPI) and maltodextrin (MD), alone or in combination, was evaluated during spray-drying of honey. No powder was recovered when pure honey was spray-dried. Honey powders were successfully obtained (powder recovery >50%) by adding MD and WPI alone at a Honey: MD ratio of 40:60 or at a Honey:WPI ratio of 70:30. The addition of a small amount of WPI (as low as 0.5% w/w) to MD reduced the amount of carriers required to spray-dry honey. Powder recovery increased from 0 (Honey:MD:WPI = 60:40:0) to 57.4 ± 4.7% when MD was replaced by 0.5% WPI (Honey:MD:WPI = 60:39.5:0.5). The surface tension of feed solutions, surface elemental composition, and glass transition temperature of spray-dried honey powders was analyzed. The mechanisms of such a significant effect of WPI on spray-drying of honey are attributed to the preferential migration of protein to the droplet/air interface and the limited inward movement of protein during moisture evaporation, in conjunction with excellent skin-forming properties of protein upon drying. Powders' moisture content, water activity, and hygroscopicity were negligibly influenced by different carriers. Bulk density and particle size were positively affected by MD concentration, which might be related to agglomeration process of particles.